Acid-catalyzed C–O coupling of styrenes with N-hydroxyphthalimide: trapping alkenyl radicals by TEMPO. Issue 22 (2nd June 2016) - Xia, Xiao-Feng; Zhu, Su-Li; Niu, Yan-Ning; Zhang, Danting; Liu, Xiang; Wang, Haijun
Abstract: A mild metal-free acid-catalyzed 1, 2-dihydroxylaminations of alkenes with N -hydroxyphthalimide and 2, 2, 6, 6-tetramethylpiperidine N -oxyl (TEMPO) has been demonstrated under air conditions to furnish the dioxygenated products in good to excellent yields. The dioxygenated product can be easily transformed into ketone derivative using 3-chloroperbenzoic acid ( m -CPBA) as the oxidant in a high yield. Graphical abstract: